History, Purpose, and Character Values in The Basapa Tradition in the Beginning of Padang Pariaman Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This Basapa tradition is no stranger to the people of Pariaman, the Basapa tradition is carried out as an expression of gratitude and thanks to Sheikh Burhanuddin, for his success in developing Islamic teachings in Minangkabau. Character is a value that is instilled in a person which is obtained from experience, education, sacrifice, trials, and environmental influences which are then combined with the values that exist within a person and become intrinsic values that are embodied in the fighting power system which then becomes attitudes, behavior, and thoughts of a person. Basapa tradition provides character values that can be applied in everyday life. This value is taken from the history of Syekh Burhanuddin which has become a Basapa tradition in Padang Pariaman Regency. This research method is to use a qualitative descriptive type approach. The results of this study are character values that can be used as lessons or applied are (1) religious character, (2) integrity, (3) independence, (4) nationalism, and (5) mutual cooperation.